Pengelolaan Kapasitas Layanan Untuk Perencanaan Infrastruktur Teknologi Informasi Pada PT Samudra - Dwi Selvi (CV. RO BEMA, 2024)
Management of Information Technology service capacity is an activity carried out to manage the capacity and availability of Information Technology services which begins with a supervisory process that aims to determine duties, functions and responsibilities as well as standard work procedures, develop methods for calculating the level of availability of Information Technology services that aim to calculate availability of a complex system/service, creation of a supervisory technical parameter matrix that aims to determine the parameters, tools and tools used in performance monitoring techniques, as well as preparation of a supervisory report format that aims to obtain data on the results of monitoring the capacity and availability of Information Technology services. The IT-IL Framework is a best practice framework for managing integrated and process-based Information Technology services, as well as a series of concepts and techniques for managing Information Technology infrastructure, development and operations. Management of service capacity with the IT-IL Framework in the preparation of Information Technology infrastructure at PT. Samudra needs to be done to ensure the achievement of results from the planning and implementation of Information Technology services.